INCENTIVE MECHANISM FOR QUALITY INSPECTION: A LINEAR PROGRAMMING APPROACH - I Nyoman Sutapa; I Gede Riana; Magdalena Wullur; Indriati Njoto Bisono (Faculty of Economics and Business Udayana University, 2025)
This study develops an incentive mechanism model for outsourced personnel in product quality inspection, based on a principal-agent relationship. The core challenge lies in misaligned incentives, where agents often prioritize output volume over quality. By integrating Mechanism Design Theory (MDT) and Linear Programming (LP), our model aligns the principal's objective of minimizing defective products with the agent's utility maximization, subject to Incentive Compatibility and Individual Rationality constraints. Our analysis reveals that the optimal incentive structure combines a basic wage with a performance-based bonus. The optimal effort level of outsourced personnel increases with both rising losses due to defective products and enhanced detection effort effectiveness. The model also shows that optimal inspection allocation should be assigned to personnel with higher capabilities, especially for high-risk products. This research provides a theoretical contribution by integrating MDT and LP for incentive design and offers practical implications for improving product quality through a measurable incentive framework.